Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.4028/www.scientific.net/kem.230-232.267
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Asymmetry of AZ31 Wrought Magnesium Alloy

Abstract: In this work, the mechanical behaviour of an AZ31 wrought magnesium alloy due to tensile, compressive and four-point bending tests was analysed. Several specimens of this material were taken in different directions from a rolled plate. Tensile and compression tests allowed to characterise the mechanical properties of the material in the rolling and cross rolling directions. To take the effect of the anisotropy induced by the rolling procedure itself into account, the bending tests were carried out using specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 5 publications
4
23
0
Order By: Relevance
“…This is attributed to the tensile and compressive yield asymmetry observed in wrought magnesium alloys. [33] Plots of mean stress vs the number of cycles for each strain ratio are shown in Figure 16. It is evident that at the lower strain ratio smaller mean stress evolved and the mean stress increased until 600 cycles, which was close to the half-life cycle.…”
Section: E Effect Of Strain Ratiomentioning
confidence: 99%
“…This is attributed to the tensile and compressive yield asymmetry observed in wrought magnesium alloys. [33] Plots of mean stress vs the number of cycles for each strain ratio are shown in Figure 16. It is evident that at the lower strain ratio smaller mean stress evolved and the mean stress increased until 600 cycles, which was close to the half-life cycle.…”
Section: E Effect Of Strain Ratiomentioning
confidence: 99%
“…Nobre et al 8) have reported that bending strength values of 200-220 MPa were obtained for a compressive strain of 2.5% using the 4-point bending test on AZ31 wrought magnesium alloys (length of 160 mm, width of 15 or 20 mm, and thickness of 10 mm).…”
Section: Bending Strengthmentioning
confidence: 99%
“…al., 2007;Knezevic et al, 2010). The compressive hardening behavior of Mg sheet is characterized by an S-shaped sigmoidal hardening curve exhibiting a low initial yield stress (Nobre et al, 2002) followed by a concave-up stress-strain behavior with a low initial hardening rate due to extension twinning (Yukutake et al, 2003). At large compressive strain, due to the exhaustion of twinning and M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 dominance of slip mechanisms, the stress strain curve switches to that of a typical concave-down shape (Yukutake et al, 2003;Lou et.…”
Section: Introductionmentioning
confidence: 99%